2022
DOI: 10.3390/cancers14235847
|View full text |Cite
|
Sign up to set email alerts
|

Conventional vs. Drug-Eluting Beads Transarterial Chemoembolization for Unresectable Hepatocellular Carcinoma—A Propensity Score Weighted Comparison of Efficacy and Safety

Abstract: This study compared the efficacy and safety of conventional transarterial chemoembolization (cTACE) with drug-eluting beads (DEB)-TACE in patients with unresectable hepatocellular carcinoma (HCC). This retrospective analysis included 370 patients with HCC treated with cTACE (n = 248) or DEB-TACE (n = 122) (January 2000–July 2014). Overall survival (OS) was assessed using uni- and multivariate Cox proportional hazards models and Kaplan-Meier analysis. Additionally, baseline imaging was assessed, and clinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…In the present study, survival did not differ significantly between the patients who underwent cTACE and those who underwent DEB-TACE. Similar results have been reported in some other studies and meta-analyses ( 15 , 19 - 22 ) . A large, multicenter randomized clinical trial conducted by Golfieri et al ( 15 ) (of the Precision Italia Study Group) showed that both techniques are equally effective and safe, with similar oneand two-year survival rates-86.2% and 56.8%, respectively, for DEB-TACE and 83.5% and 55.4%, respectively, for cTACE.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, survival did not differ significantly between the patients who underwent cTACE and those who underwent DEB-TACE. Similar results have been reported in some other studies and meta-analyses ( 15 , 19 - 22 ) . A large, multicenter randomized clinical trial conducted by Golfieri et al ( 15 ) (of the Precision Italia Study Group) showed that both techniques are equally effective and safe, with similar oneand two-year survival rates-86.2% and 56.8%, respectively, for DEB-TACE and 83.5% and 55.4%, respectively, for cTACE.…”
Section: Discussionsupporting
confidence: 92%
“…Savic et al compared the efficacy and safety of conventional and drug-eluting beads (DEB) trans-arterial chemoembolization (TACE) [ 8 ]. Although there were no significant differences in overall survival in conventional TACE and DEB-TACE, infiltrate or nodular features affected the overall survival.…”
mentioning
confidence: 99%